Deficiência e insuficiência sérica de 25-Hidroxivitamina D [25(OH)D] são fatores de risco para incidência de dinapenia em indivíduos com 50 anos e mais? - Delinocente, Maicon Luís Bicigo (2021)
BACKGROUND: Epidemiological studies that demonstrated the association between low concentrations of 25(OH)D and reduction in neuromuscular strength (dynapenia) as age advances are few and controversial. The vast majority of them are cross-sectional studies, which do not allow establishing a causal relationship, and which present important methodological divergences, such as different cutoffs to define low neuromuscular strength as well as different thresholds to define low serum concentrations of 25(OH)D. The only longitudinal study that we are aware of has not confirmed this association and, to date, we have not observed studies that analyzed whether the diagnosis of osteoporosis and vitamin D supplementation could modify these associations. OBJECTIVES: i) To analyze whether serum 25(OH)D deficiency and insufficiency are risk factors for the incidence of dynapenia in people aged 50 and over; ii) To analyze whether these associations are modified with the withdrawal of individuals diagnosed with osteoporosis or who were supplemented with vitamin D from our analyzes. METHOD: Longitudinal study involving 3,205 participants in the English Longitudinal Study of Ageing (ELSA Study), non-dynapenic at baseline and followed for four years. Vitamin D, also assessed at baseline by the serum concentration of 25(OH)D, was classified as sufficient (> 50 nmol/L), insufficient (≥ 30 and ≤ 50 nmol/L) and deficient (< 30 nmol/L). The incidence of dynapenia was considered when the handgrip strength was < 26 kg for men and < 16 kg for women at the end of the four-year follow-up. Poisson regression models were adjusted for sociodemographic, behavioral, clinical and biochemical characteristics. RESULTS: Serum deficiency of 25(OH)D was a risk factor for the incidence of dynapenia (IRR = 1.70 95%CI 1.04 – 2.79), as well as age from 70 to 79 years (IRR = 3.89 95%CI 1,61 – 9.44), 80 years and over (IRR = 8.07 95%CI 3.05 – 21.36), presence of osteoporosis (IRR = 1.76 95%CI 1.02 – 3.03) and low levels serum IGF-1 (IRR = 1.76 95%CI 1.02 – 3.04). When only individuals without osteoporosis or who did not undergo vitamin D supplementation were analyzed, both the deficiency (IRR = 1.78 95%CI 1.01 – 3.13) and insufficiency of 25(OH)D (IRR = 1.77 95%CI 1.06 – 2.94) were risk factors for the incidence of dynapenia, as well as the age from 70 to 79 years (IRR = 5.15 95%CI 1.77 – 14.97), 80 years and more (IRR = 8.55 95%CI 2.66 – 27.51), low serum IGF-1 levels (IRR = 1.94 95%CI 1.05 – 3.61), low appendicular skeletal muscle mass index (ASMI) (IRR = 2.12 95%CI 1.07 – 4.19) and hight waist circumference (IRR = 1.97 95%CI 1.08 – 3.59). CONCLUSION: Serum level of 25(OH)D < 30 nmol / L is a risk factor for the incidence of dynapenia. In those individuals without osteoporosis or who do not take vitamin D supplementation, the risk threshold is higher (≤ 50 nmol / L). In addition to osteoporosis and vitamin D supplementation modifying the effect of the associations found, older age groups, low serum IGF-1 concentrations, low ASMI and hight waist circumference are among the risk factors identified for the incidence of dynapenia in four years of follow-up.